Penguatan Perlindungan Hukum Pegawai Aparatur Sipil Negara melalui Rekonstruksi Banding Adminsitrasi - Ahmad Aniq; Yos Johan Utama; Nabitatus Sa’adah (Universitas Negeri Semarang, 2026)
Administrative appeals as an administrative effort by State Civil Apparatus (ASN) employees who are dissatisfied with the decision to dismiss employees are questioned as to their usefulness in providing legal protection to civil apparatus. This study aims to reveal the construction of an administrative appeal format for the decision to dismiss or terminate the employment of State Civil Apparatus employees that provides more legal protection for ASN employees. Administrative appeals are not merely additional formal requirements before a dispute is examined by a state administrative court but it is truly substantive in its testing and its decision is fully respected. This study is a normative-empirical study that begins with a normative analysis of primary, secondary, and tertiary legal materials based on a conceptual approach and statutory regulations. Then, It uses a sociological approach to obtain primary data through observation and data collection from informants. The desired result is to provide a prescription for the ideal formulation of legal protection for ASN employees through administrative appeals. The results of the study indicate that in order for administrative appeals to truly provide protection for ASN employees from arbitrary actions by officials, several improvements are needed, namely increasing the composition of BPASN members, examining disputes from a material perspective rather than just a formal examination, clarifying the procedural rules so that ASN employees feel transparent about the resolution and ensuring that administrative decision is complied with and implemented.